ER-Phagy and Microbial Infection - Li, Jiahui; Gao, Enfeng; Xu, Chenguang; Wang, Hongna; Wei, Yongjie (Frontiers in Cell and Developmental Biology, 2021)
The endoplasmic reticulum (ER) is an essential organelle in cells that synthesizes, folds and modifies membrane and secretory proteins. It has a crucial role in cell survival and growth, thus requiring strict control of its quality and homeostasis. Autophagy of the ER fragments, termed ER-phagy or reticulophagy, is an essential mechanism responsible for ER quality control. It transports stress-damaged ER fragments as cargo into the lysosome for degradation to eliminate unfolded or misfolded protein aggregates and membrane lipids. ER-phagy can also function as a host defense mechanism when pathogens infect cells, and its deficiency facilitates viral infection. This review briefly describes the process and regulatory mechanisms of ER-phagy, and its function in host anti-microbial defense during infection.